RETRACTED: Multimedia Presentations Through Digital Storytelling for Sustainable Development of EFL Learners’ Argumentative Writing Skills, Self-Directed Learning Skills and Learner Autonomy - Salem, Ashraf Atta Mohamed S. (Frontiers in Education, 2022)
The present study explored the impact of online digital storytelling on developing EAP students' argumentative writing skills, and its impact on improving self-directed learning skills and learner autonomy in language learning. To reach such ends, standardized pretest and posttest in argumentative writing skills was designed, which depends on the writing tasks of IELTS task 2 and Independent TOEFL test writing tasks. Also, self-rating scale of self-directed learning and language Leaner Autonomy Scale (LAS) have been exploited. The two experimental groups were trained to write using two different types of learning; group A through an online storytelling and the group B used offline content producing software to produce digital storytelling to promote writing skills. On the other hand, the control group (group C) used traditional storytelling approach. Results primarily revealed that the literacy skills of those who produced their stories with the offline software (group B) improved significantly in comparison to the other experimental group which was taught through an online digital storytelling (group A). The control group achieved the least of the three groups in developing target skills. Further, the qualitative analysis of experimental group members' responses in the semi-structured interviews revealed positive attitudes towards learning through blended learning approaches compared with pure online web-based learning. It is, therefore, recommended that blended learning should be used for students from communities with poor digital literacy and technology infrastructure. Also, online learning should be used with care to cope with community needs so as to fill a real gap in field practices in language learning to improve multiliteracy skills.